ANALISIS HISTORIS-KRITIS TERHADAP PERPECAHAN KERAJAAN ISRAEL DALAM KITAB 1 RAJA-RAJA 12:1-19 - Ravedly Chavelier Tiku Pasang; Fanni Evata; Rismayardiyani (Jurnal Salome : Multidisipliner Keilmuan, 2026)
The historical-critical approach is a method of interpreting a biblical text by examining its historical, social, and political background at the time the events occurred. The author applies this approach to 1 Kings 12:1-19, which narrates the division of the Kingdom of Israel after the death of Solomon. The people’s rejection of King Rehoboam was driven by policies that increasingly burdened them, such as high taxes and forced labor, leading to disappointment and anger and ultimately prompting them to separate. Through this approach, it can be understood that the division of the kingdom was not caused solely by spiritual factors, but also by social and political issues. The historical-critical method helps readers understand the Bible more clearly, contextually, and in a way that is relevant to present-day life, especially in recognizing the importance of just and wise leadership.